2004
DOI: 10.1523/jneurosci.1437-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Pallidal Representation of Pavlovian Cues and Reward: Population and Rate Codes

Abstract: We recorded neural activity in the ventral pallidum (VP) while rats learned a pavlovian reward association. Rats learned to distinguish a tone that predicted sucrose pellets (CSϩ) from a different tone that predicted nothing (CSϪ). Many VP units became responsive to CSϩ, but few units responded to CSϪ. When two CSϩ were encountered sequentially, the earliest predictor of reward became most potent. Many VP units were also activated when the sucrose reward was received [unconditioned stimulus (UCS)]. These VP un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
128
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 49 publications
15
128
0
Order By: Relevance
“…Problematically, however, it has never been clear how NAc-VP circuitry could distinguish various reward signals from each other. Existence of multiple anatomical loops connecting the NAc and VP provides a way to segregate the mixture of reward components, but some NAc and VP subregions and single neurons may also need to represent more than one signal (6,35,47). Here, we find that disentangling of signals can still be faithfully achieved.…”
mentioning
confidence: 74%
“…Problematically, however, it has never been clear how NAc-VP circuitry could distinguish various reward signals from each other. Existence of multiple anatomical loops connecting the NAc and VP provides a way to segregate the mixture of reward components, but some NAc and VP subregions and single neurons may also need to represent more than one signal (6,35,47). Here, we find that disentangling of signals can still be faithfully achieved.…”
mentioning
confidence: 74%
“…The pallidum has seldom been reported in functional imaging studies of reward (Elliott et al, 2000), but comparative research has shown that this area is an important component of the neural systems underlying food motivation and hedonics (McAlonan et al, 1993;Pecina and Berridge, 2000;Tindell et al, 2004;Smith and Berridge, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This alternative draws on the distinction between phasic dopamine signals (spike-triggered release limited to within synapses) and tonic dopamine signals (spike-independent release extending outside synapses) and typically assigns a learning role specifically to phasic signals (Grace 1991;Grace et al 2007;Niv et al 2007;Phillips et al 2003;Schultz 1997;. Learning and prediction roles of dopamine have been conceptualized as teaching signals, S-S prediction signals about future rewards, and S-R stamping-in or habit reinforcement ( Schultz et al 1997;Tobler et al 2005) and by target systems in nucleus accumbens and related forebrain structures (Aldridge et al 1993;Barnes et al 2005;Carelli 2004;Cromwell et al 2005;Day and Carelli 2007;Ghitza et al 2004;Roitman et al 2005;Taha and Fields 2006;Tindell et al 2004;Wan and Peoples 2006).…”
Section: Controversial Subcortical Pleasure Generators? Dopamine and mentioning
confidence: 99%